แบบจำลองทางพลศาสตร์ของแขนกลที่มีความหยุ่นตัวที่ใช้ในงานระยะเอื้อมไกล - เด่นชัย วรเดชจำเริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research work is to find the dynamic model of a manipulator arm with two flexible links. The derived model is intent to use as a mathematical model of real-time controller design. The manipulator is designed so that it is suitable for long reach tasks. The links are formed using a five-bar linkage. The actuators, direct-drive DC motor, are located at the base of the manipulator so that the loads, due to the weight of the motors, do not affect the driving torque of the motors. The dynamic model is derived base on the fact that the accelerometers are attached to the tips of the elastic link. The dynamic model is derived using Lagrange equation method. With assumptions purposed in this work, the very complication dynamic model is reduced to a mass-spring linked model. The reduced dynamic model can be described in state equation. And for our configuration, using five-bar linkage, it is shown that one of the flexible links, link 1 attached to a motor, is rigid compare to the long reach linkage, link 4 in our configuration. From the results of simulation based on the derived dynamic model, it is shown that the derived model is proper for use as the model for designing of real-time controllers